The functions of human saliva: A review sponsored by the World Workshop on Oral Medicine VI - Dawes, C.; Pedersen, A.M.L.; Villa, A.; Ekström, J.; Proctor, G.B.; Vissink, A.; Aframian, D.; McGowan, R.; Aliko, A.; Narayana, N.; Sia, Y.W.; Joshi, R.K.; et al. (Archives of oral biology, 2015)
•A narrative review was carried out of the functions of human saliva.•Saliva moistens and lubricates the mouth and is important for taste and smell.•Saliva protects the teeth and the oral and oesophageal mucosa in many ways.•Saliva has antibacterial and wound healing properties. This narrative review of the functions of saliva was conducted in the PubMed, Embase and Web of Science databases. Additional references relevant to the topic were used, as our key words did not generate references which covered all known functions of saliva. These functions include maintaining a moist oral mucosa which is less susceptible to abrasion, and removal of micro-organisms, desquamated epithelial cells, leucocytes and food debris by swallowing. The mucins form a slimy coating on all surfaces in the mouth and act as a lubricant during such processes as mastication, formation of a food bolus, swallowing and speaking. Saliva provides the fluid in which solid tastants may dissolve and distributes tastants around the mouth to the locations of the taste buds. The hypotonic unstimulated saliva facilitates taste recognition. Salivary amylase is involved in digestion of starches. Saliva acts as a buffer to protect oral, pharyngeal and oesophageal mucosae from orally ingested acid or acid regurgitated from the stomach. Saliva protects the teeth against acid by contributing to the acquired enamel pellicle, which forms a renewable lubricant between opposing tooth surfaces, by being supersaturated with respect to tooth mineral, by containing bicarbonate as a buffer and urea and by facilitating clearance of acidic materials from the mouth. Saliva contains many antibacterial, antiviral and antifungal agents which modulate the oral microbial flora in different ways. Saliva also facilitates the healing of oral wounds. Clearly, saliva has many functions which are needed for proper protection and functioning of the human body.